Inhibition effect of environmentally benign Kuchla (Strychnos Nuxvomica) seed extract on corrosion of mild steel in hydrochloric acid solution - Singh A.; Singh V.K.; Quraishi M.A. (My University, 2025)
The inhibition of the corrosion of mild steel in hydrochloric acid solution by the seed extract of Kuchla (Strychnos Nuxvomica) has been studied using weight loss, electrochemical impedance spectroscopy, potentiodynamic polarization and linear polarization techniques. Inhibition was found to increase with increasing concentration of the extract. The effect of temperature, immersion time and acid concentration on the corrosion behavior of mild steel in 1 M HCl with addition of extract was also studied. The adsorption of the extract on the mild steel surface obeyed the Langmuir adsorption isotherm. Values of inhibition efficiency calculated from weight loss, potentiodynamic polarization, and electrochemical impedance spectroscopy (EIS) are in good agreement. Polarization curves showed that Kuchla (Strychnos Nuxvomica) seed extract behaves as a mixed-type inhibitor in hydrochloric acid. The activation energy as well as other thermodynamic parameters for the inhibition process was calculated. The adsorbed film on mild steel surface containing Kuchla (Strychnos Nuxvomica) seed extract inhibitor was also measured by Fourier transform infrared spectroscopy (FTIR). The results obtained showed that the seed extract of Kuchla (Strychnos Nuxvomica) could serve as an effective inhibitor of the corrosion of mild steel in hydrochloric acid media. © 2010 RASĀYAN. All rights reserved.